Cytoskeletal Modulation of Lipid Interactions Regulates Lck Kinase Activity - Chichili, Gurunadh R. (American Society for Biochemistry and Molecular Biology, 2012)
The actin cytoskeleton promotes clustering of proteins associated with cholesterol-dependent rafts, but its effect on lipid interactions that form and maintain rafts is not understood. We addressed this question by determining the effect of disrupting the cytoskeleton on co-clustering of dihexadecyl-(C(16))-anchored DiO and DiI, which co-enrich in ordered lipid environments such as rafts. Co-clustering was assayed by fluorescence resonance energy transfer (FRET) in labeled T cells, where rafts function in the phosphoregulation of the Src family kinase Lck. Our results show that probe co-clustering was sensitive to depolymerization of actin filaments with latrunculin B (Lat B), inhibition of myosin II with blebbistatin, and treatment with neomycin to sequester phosphatidylinositol 4,5-bisphosphate. Cytoskeletal effects on lipid interactions were not restricted to order-preferring label because co-clustering of C(16)-anchored DiO with didodecyl (C(12))-anchored DiI, which favors disordered lipids, was also reduced by Lat B and blebbistatin. Furthermore, conditions that disrupted probe co-clustering resulted in activation of Lck. These data show that the cytoskeleton globally modulates lipid interactions in the plasma membrane, and this property maintains rafts that function in Lck regulation.